THE IMPACT OF DIGITALIZATION ON FINANCIAL TECHNOLOGY DEVELOPMENT - BOZHENKO, VICTORIA; PIHUL, YEVGENII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The rapid growth of digital technologies, increasing Internet coverage and improving its quality is the basis of the Industry 4.0, which permeates the financial system. The emergence of new entrants to the financial services market enhances market competition and the search for innovative ways to meet customer needs. The article is devoted to the impact digital technologies on the financial technologies, as well as the analysis of the main trends in the development of the financial technology market in Ukraine and the world. The article highlights and substantiates the main drivers of finance digitalization. The authors of the article analyze the impact of new technologies (blockchain, big data, cloud technologies, artificial intelligence and machine learning, biometric technologies, virtual reality technologies) on the transformation of such areas of financial relations as payments and remittances, financing and lending, wealth management, insurance, communication with clients of financial institutions, as well as security and protection. The COVID-19 pandemic has also made adjustments to the financial systems around the world, including the provision of digital financial services and the organization of the FinTech market. On the one hand, the demand for digital financial products has almost doubled, and on the other hand, the volume of investments in the fintech industry in the world in 2020 has decreased by a third. The authors of the article pay special attention to cyber-fraud as one of the key threats to digitalization, which have negative consequences for the stable functioning of financial service providers and their consumers, namely: loss of information, lack of access, unauthorized interference in corporate information systems, dissemination of personal financial information about customers, etc. The results of this study can be useful for regulators and supervisors of financial institutions in decision-making to stimulate the development of FinTech-solutions, as well as financial companies in improving their strategy in the transition to the digital development model.